Moral Education as a Foundation for Character Development in Grade 6 Students - Wandira, L. Jaka; Sugiyat, Sugiyat; Nurhidayati, Indah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine 1) Implementation of moral education in shaping the character of 6th grade students of SD Negeri 3 Masaran, 2) Supporting and inhibiting factors faced in shaping the morals of 6th grade students of SD Negeri 3 Masaran, 3) Solutions in overcoming obstacles that occur in shaping the morals of 6th grade students of SD Negeri 3 Masaran. This research uses a qualitative method with a descriptive approach. The results of the study can be concluded that 1) The role of moral education in shaping the character of 6th grade students of SD Negeri 3 Masaran is done by exemplary, habituation, advice and punishment, and using inspirational stories. 2) Supporting factors in the formation of student character are competent teachers, playmates, a supportive environment, adequate facilities and infrastructure, while the inhibiting factor is still low student awareness. 3) The solution in overcoming the obstacles that occur is to improve their attitude first and be taught about good attitudes so that they are practiced in everyday life.